Two Aspects of Feedforward Control During a Fencing Lunge: Early and Anticipatory Postural Adjustments - Akbaş, Anna; Marszałek, Wojciech; Bacik, Bogdan; Juras, Grzegorz (Frontiers in Human Neuroscience, 2021)
The present study investigated whether the expertise in fencing influence the onset of postural preparation during fencing lunge, and how it changes under different performance condition. We also questioned if the onset of feedforward control can be categorized into one of the postural phases – anticipatory or early postural adjustment. Eight elite fencers and nine physical education students performed an attack with a lunge in self-paced and reaction time conditions from three different initial stance widths. The onset of the center of pressure (COP) displacement and EMG activities for the tibialis anterior (TA) of both limbs were recorded. The results show that the expertise in fencing delay the onset of the activity of TA of the front leg and the onset of COP displacement during fencing lunge performance in comparison to controls. Additionally, in opposite to control group, fencers produce typical APA pattern in the activation of TA under different performance condition – delayed under reaction time in comparison to self-initiated lunging, and constant time of APA onset under different widths of stance. According to different time and function of TA activity and COP displacement in lunging, we propose to address them as anticipatory postural adjustment and early postural adjustment, respectively.